2002
DOI: 10.1302/0301-620x.84b3.0840401
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the Kotz type of tumour endoprosthesis for the lower limb

Abstract: I n 251 patients over a period of 15 years an uncemented Kotz modular femoral and tibial reconstruction mega prosthesis was implanted after resection of a malignant tumour of the lower limb. Twenty-one patients (8.4%) underwent revision for aseptic loosening, again using an uncemented prosthesis, and five of these required a further revision procedure. The median follow-up time from the first revision was 60 months (11 to 168) and after a second revision, 33 months (2 to 50). The probability of a patient avoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 8 publications
(8 reference statements)
1
32
0
1
Order By: Relevance
“…These included 26 Kotz Modular Femur Tibia Reconstruction System (KMFTR 1 ; Stryker-Howmedica Inc, Mahwah, NJ, USA), 188 Howmedica Modular Resection System (HMRS; Howmedica GmBH, Kiel, Germany), and 33 Global Modular Replacement System (GMRS, Stryker GmbH & Co KG, Duisburg, Germany). The major differences are represented by continuously adapted stem designs and the modular rotating hinge mechanism of the more recent generations that replaced the fixed hinge mechanism of the older devices for replacement of the knee [6,11,14,15,18]. In all but 11 implants, cementless fixation was used.…”
Section: Implantsmentioning
confidence: 99%
See 2 more Smart Citations
“…These included 26 Kotz Modular Femur Tibia Reconstruction System (KMFTR 1 ; Stryker-Howmedica Inc, Mahwah, NJ, USA), 188 Howmedica Modular Resection System (HMRS; Howmedica GmBH, Kiel, Germany), and 33 Global Modular Replacement System (GMRS, Stryker GmbH & Co KG, Duisburg, Germany). The major differences are represented by continuously adapted stem designs and the modular rotating hinge mechanism of the more recent generations that replaced the fixed hinge mechanism of the older devices for replacement of the knee [6,11,14,15,18]. In all but 11 implants, cementless fixation was used.…”
Section: Implantsmentioning
confidence: 99%
“…The frequency of limb salvage surgery for patients with primary bone malignancies using modular endoprostheses has steadily increased during the last decades and during this time, endoprosthetic survival has improved because of advances in design, manufacturing, and surgical techniques [15]. However, complication rates are still high as a result of a variety of factors including factors such as the large dead space in the tumor bed surrounding the prosthesis, wide soft tissue exposure, fixation issues of the implants, and immune suppression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvements in implant design and manufacturing and advances in surgical techniques [21] and adjuvant treatments for malignancies have resulted in limb-salvage surgery after tumor resection becoming a standard approach. Modular endoprosthetic reconstruction of single joints has become a well-established treatment option, especially for patients needing hip or knee reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the studies reported results for total femur replacements together with partial femur reconstructions, which makes it difficult to draw conclusions for total femur replacement-specific complications [1,21]. Most of the studies emphasized oncologic and functional outcomes of the patients; only a few specifically addressed the modes by which total femur replacement failed.…”
Section: Introductionmentioning
confidence: 99%